Adjuvant atezolizumab versus observation in muscle-invasive urothelial carcinoma (IMvigor010): a multicentre, open-label, randomised, phase 3 trial. Issue 4 (April 2021) - Bellmunt, Joaquim; Hussain, Maha; Gschwend, Jürgen E; Albers, Peter; Oudard, Stephane; Castellano, Daniel; Daneshmand, Siamak; Nishiyama, Hiroyuki; Majchrowicz, Martin; Degaonkar, Viraj; Shi, Yi; Mariathasan, Sanjeev; et al.
Summary: Background: Despite standard curative-intent treatment with neoadjuvant cisplatin-based chemotherapy, followed by radical surgery in eligible patients, muscle-invasive urothelial carcinoma has a high recurrence rate and no level 1 evidence for adjuvant therapy. We aimed to evaluate atezolizumab as adjuvant therapy in patients with high-risk muscle-invasive urothelial carcinoma. Method: In the IMvigor010 study, a multicentre, open-label, randomised, phase 3 trial done in 192 hospitals, academic centres, and community oncology practices across 24 countries or regions, patients aged 18 years and older with histologically confirmed muscle-invasive urothelial carcinoma and an Eastern Cooperative Oncology Group performance status of 0, 1, or 2 were enrolled within 14 weeks after radical cystectomy or nephroureterectomy with lymph node dissection. Patients had ypT2–4a or ypN+ tumours following neoadjuvant chemotherapy or pT3–4a or pN+ tumours if no neoadjuvant chemotherapy was received. Patients not treated with neoadjuvant chemotherapy must have been ineligible for or declined cisplatin-based adjuvant chemotherapy. No post-surgical radiotherapy or previous adjuvant chemotherapy was allowed. Patients were randomly assigned (1:1) using a permuted block (block size of four) method and interactive voice-web response system to receive 1200 mg atezolizumab given intravenously every 3 weeks for 16 cycles or up to 1 year, whichever occurred first, or to observation. Randomisation was stratified by previous neoadjuvant chemotherapy use, number of lymph nodes resected, pathological nodal status, tumour stage, and PD-L1 expression on tumour-infiltrating immune cells. The primary endpoint was disease-free survival in the intention-to-treat population. Safety was assessed in patients who either received at least one dose of atezolizumab or had at least one post-baseline safety assessment. This trial is registered with ClinicalTrials.gov, NCT02450331, and is ongoing but not recruiting patients. Findings: Between Oct 5, 2015, and July 30, 2018, we enrolled 809 patients, of whom 406 were assigned to the atezolizumab group and 403 were assigned to the observation group. Median follow-up was 21·9 months (IQR 13·2–29·8). Median disease-free survival was 19·4 months (95% CI 15·9–24·8) with atezolizumab and 16·6 months (11·2–24·8) with observation (stratified hazard ratio 0·89 [95% CI 0·74–1·08]; p=0·24). The most common grade 3 or 4 adverse events were urinary tract infection (31 [8%] of 390 patients in the atezolizumab group vs 20 [5%] of 397 patients in the observation group), pyelonephritis (12 [3%]) vs 14 [4%]), and anaemia (eight [2%] vs seven [2%]). Serious adverse events occurred in 122 (31%) patients who received atezolizumab and 71 (18%) who underwent observation. 63 (16%) patients who received atezolizumab had a treatment-related grade 3 or 4 adverse event. One treatment-related death, due to acute respiratory distress syndrome, occurred in the atezolizumab group. Interpretation: To our knowledge, IMvigor010 is the largest, first-completed phase 3 adjuvant study to evaluate the role of a checkpoint inhibitor in muscle-invasive urothelial carcinoma. The trial did not meet its primary endpoint of improved disease-free survival in the atezolizumab group over observation. Atezolizumab was generally tolerable, with no new safety signals; however, higher frequencies of adverse events leading to discontinuation were reported than in metastatic urothelial carcinoma studies. These data do not support the use of adjuvant checkpoint inhibitor therapy in the setting evaluated in IMvigor010 at this time. Funding: F Hoffmann-La Roche/Genentech.